Indian Renaissance : British romantic art and the prospect of India - De Almeida, Hermione, 1950-; Gilpin, George H. (Aldershot, England : Ashgate, 2005)
An examination of British artists whose travel to the subcontinent of India influenced the Romantic Movement in England. It also discuss the impact of the images on the culture of Victorian Britain. Artists discussed include James Forbes, James Wales, Tilly Kettle, William Hodges, Johan Zoffany Francesco Renaldi, Thomas and William Daniell, Robert Home, Thomas Hickey, Arthur William Devis, R. H. Colebrooke, Alexander Allan, Henry Salt, James Baillie Fraser, Charles Gold, James Moffat, Charles D'Oyly, William Blake, J. M. W. Turner and George Chinnery
The idea of India : tiger, tree, and cave -- Oriental fantasies and Indian prospects -- English romantic art and the Indian prospect -- Storming Seringapatam : the drama and romance of empire -- Thomas Daniell and the picturesque possession of India -- Dark prospects in the light of empire -- Elegies to an Indian renaissance
Includes bibliographical references (p. 327-332) and index
Keywords: Art, British -- 18th century; Art, British -- 19th century; Romanticism in art -- Great Britain; India -- In art